The Impact of E-Prescribing Use in Hospitals: A Systematic Review - Suriadi, Widyastuti; Lazuardi, Lutfan; Kristina, Susi Ari (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: Electronic prescribing (e-prescribing) systems have been increasingly adopted in hospital settings to enhance the safety, accuracy, and efficiency of medication management. These systems aim to reduce human error in prescribing and dispensing medication, which is crucial for improving patient outcomes and the overall quality of healthcare.Objectives: This study aims to evaluate the direct effects of the e-prescribing system on prescribing errors, medication errors, efficiency and effectiveness, and user acceptance among healthcare workers.Methods: The study is based on a comprehensive review of 13 articles published between 2019 and 2023, covering a range of quantitative and mixed methods studies sourced from databases such as PubMed, ScienceDirect, and Google Scholar.Results: The findings reveal that e-prescribing has a significant positive impact on reducing errors. Six of the reviewed studies reported a reduction in prescription writing errors while four studies highlighted a decrease in medication errors after the implementation of the system. Additionally, six studies demonstrated improvements in efficiency and productivity, and four studies reported positive user acceptance of the system.Conclusion: The implementation of electronic prescribing systems in hospitals has shown clear advantages in reducing errors, increasing efficiency, and receiving positive feedback from healthcare workers. This highlights the potential role of e-prescribing in improving the quality of healthcare services.